EDUCATING PRESCHOOLERS IN THE SPIRIT OF NATIONAL TRADITIONS AND NATIONAL VALUES - Fozilova Shodiyona Abdurasulovna (Bright Mind Publishing, 2025)
This article discusses the pedagogical foundations of educating preschool children in the spirit of national customs and traditions, forming a sense of compassion.
Keywords: Nationality, value, Preschool educational organizations, spirituality, national pride, national value, unity.